Effect of Teachers’ Happiness on Teachers’ Health. The Mediating Role of Happiness at Work - Benevene, Paula; De Stasio, Simona; Fiorilli, Caterina; Buonomo, Ilaria; Ragni, Benedetta; Briegas, Juan José Maldonado; Barni, Daniela (Frontiers in Psychology, 2019)
The present study aims to deepen the understanding of the effect of dispositional happiness and self-esteem, as dispositional traits, on the health of teachers, as well as to understand the role played by the working environment in generating positive affection, thus mediating between the dispositional traits and teachers’ health. Two hundred and eighty-two full-time in-service teachers (93.6% female) from Rome (Italy) took part to this study. Their age ranged from 26 to 55 (M= 40.49 years, SD= 5.93). Participants’ teaching experience ranged from 1 to 31 years (M = 9.95 years, SD = 5.65). 30.6% of participants taught in kindergartens (for children aged 0–5 years), 42.6% in primary schools (for children aged 6–11 years), 15.8% in middle schools and 10.9% in high schools. A questionnaire was administered, containing: the Subjective Happiness Scale (SHS); the Rosenberg Self-Esteem Scale (RSES); The adapted version for teachers of the School Children Happiness Inventory; the Physical and Mental Health Scales (SF12). The data gathered were analysed using PASW Statistic version 24.0 (SPSS). Our results showed that teacher happiness at work partially mediates the relationship between dispositional happiness and teacher health, as well as the relationship between self-esteem and teacher health. To the best of our knowledge, the mediational role of teacher happiness has not been addressed before with regard to these dimensions. At the same time, our findings confirmed the role of self-esteem in endorsing health-related behaviours, thus promoting physical and mental health. Moreover, according to our study findings, when teachers acknowledge their workplace as a context in which they feel happy, the impact of dispositional happiness and self-esteem on health conditions is higher. Effective measures to promote teachers’ well-being are discussed.